DISHARMONISASI KEPOLISIAN DAN KEJAKSAAN DALAM PENERAPAN KEADILAN RESTORATIF UNTUK PENYELESAIAN PERKARA PIDANA - kapitan, Rian Van Frits (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research focuses on the form of disharmony in the implementation of restorative justice by the Police and Prosecutor's Office in resolving criminal cases. Forms of disharmony in the application of restorative justice by the Police and the Prosecutor's Office in resolving criminal cases are: first, the application of restorative justice by the Police is only aimed at the actions of perpetrators who are not classified as repeat criminal acts based on court decisions, while the Prosecutor's Office requires that restorative justice be applied if the suspect commits it for the first time. criminal act. Second, the Police do not provide limits regarding the threat of punishment for criminal acts that can be resolved through the application of restorative justice, while the Prosecutor's Office explicitly determines that criminal acts that can be closed by law or whose prosecution is terminated are criminal acts that are only punishable by a fine or not punishable by imprisonment. more than 5 (five) years and thirdly, the Prosecutor's Office sets a limitation that criminal acts that can be resolved using restorative justice must be criminal acts with the value of evidence or not. The crime results in a loss value for the victim of no more than Rp. 2,500,000.00 (two million five hundred thousand rupiah) while the Police do not set a limit on the value of evidence and the value of losses experienced by the victim as a condition for terminating the investigation and the investigation using restorative justice.